The Influence of Financial Technology on Increasing Financial Inclusion in MSMEs in Bira Village, Bulukumba Regency - Kasmita Kasmita; Asri Jaya; Firman Syah (Pustaka Digital Indonesia, 2026)
This study is urgent because understanding how financial technology influences financial inclusion can help MSMEs in Bira Village overcome limited access to formal financial services and support inclusive local economic growth. This study investigates the impact of financial technology (fintech) on enhancing financial inclusion among Micro, Small, and Medium Enterprises (MSMEs) in Bira, Bulukumba Regency. The research is motivated by the limited access of MSMEs to formal financial services and the potential of fintech to offer more accessible digital financial solutions. A quantitative research method was employed, utilizing a survey approach. Data were collected through questionnaires administered to 64 MSME respondents and analyzed using simple linear regression with SPSS software. The data were collected from selected MSME operators using a purposive sampling technique The findings reveal that fintech exerts a positive and statistically significant influence on financial inclusion, as evidenced by a p-value of 0.000 and a coefficient of determination (R²) of 0.893. This indicates that 89.3% of the variance in financial inclusion is attributable to fintech adoption. The study concludes that fintech facilitates access to formal financial services such as digital payments, savings, and loans thereby promoting more efficient and sustainable business operations for MSMEs.